Thomas Goode Jones : Race, Politics, and Justice in the New South - Aucoin, Brent J. (Brent Jude) (Book collections on Project MUSE., 2016)
"Thomas Goode Jones of Alabama is the first comprehensive biography of a key Alabama politician and federal jurist whose life and times embody the conflicts and transformations in the Deep South between the Civil War and World War I"--